Problematika Hukum Penerapan Ketentuan Percepatan Penyelesaian Kasus Perambahan Hutan Di Wilayah Provinsi Riau - Yeni Elviani; Erdianto Effendi; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Provisions regarding the acceleration of settlement of forest encroachment cases have been regulated in the Law of the Republic of Indonesia Number 18 of 2013 concerning Prevention and Eradication of Forest Destruction Article 39, while investigators of PPNS, POLRI and Public Prosecutors in Riau province find it difficult to obtain evidence to resolve cases of criminal acts of forest encroachment. The dossier handed over to the Public Prosecutor is not yet complete with P-18, so there are still many criminal cases of forest encroachment that have not been resolved.This research is a sociological legal research, this research was conducted at the Center for Security and Enforcement of Environmental and Forestry Laws in Sumatra Region. While the population and sample are all parties who have a relationship with the problem in this study. Sources of data used include primary, secondary, and tertiary materials. Data collection techniques in this study were carried out by questionnaires, interviews, and literature studies.The results of this study indicate, First, the application of the provisions for the acceleration of settlement of forest encroachment cases in the Riau province area has not been maximized, there are still many cases that have not been completed because the P-21 file is not complete. Second, the Implications of the Law of the Republic of Indonesia Number 18 of 2013 concerning Prevention and Eradication of Forest Destruction has provided a legal umbrella for PPNS, POLRI and Public Prosecutors to coordinate in eradicating forest encroachment actors carried out by individuals and groups who destroy forests, especially in Riau province. Third, efforts to overcome legal problems in the application of Article 39 of the Law of the Republic of Indonesia Number 18 of 2013 concerning Prevention and Eradication of Forest Destruction in Riau Province, The Public Prosecutor has the authority to conduct a pre-prosecution if there are deficiencies in the investigation by taking into account the provisions of Article 110 Paragraph (3) and (4).Keywords: Forest-Encroachment-Investigation